Gerakan Filantropi Dalam Peningkatan Aksesibilitas Pendidikan Agama Islam (PAI) Di Banten (Desa Jambu Karya, Kabupaten Tangerang, Banten) - Misbahuddin, Misbahuddin; Wahyudin, Wawan; Muhajir (AL MURABBI, 2023)
This study aims to determine the Philanthropic Movement in improving the accessibility of Islamic education in Banten province, especially Jambu Karya Village, Tangerang Regency. This research uses an observational approach where researchers make direct observations of the learning process and education system in madrasas, mosques, or other Islamic education institutions in Jambu Karya Village. Based on direct observations made by researchers, it is known that one of the philanthropic movements that helps the availability of teaching materials is beyond the costs obtained from the government such as BOS funds or waqf or philanthropic institutions such as Dompet Duafa or Baznas is the habit of infaq for students, teachers and staff at one of the Jambu Karya Village schools, namely MTS Al Maghfiroh every Friday morning. In addition, one of the Indonesian Literacy School philanthropic organizations also helped in terms of coaching activities for local teachers, especially in Jambu Karya Village. Thus, teacher training, supporting innovative teaching methods and better resources are needed to create a better learning environment. Efforts to improve access to Islamic education in the village include financial donations, material assistance and additional training for teachers, with impact evaluation and more in-depth analysis as suggestions for future research